ANALISIS RISIKO KESEHATAN LINGKUNGAN PAJANAN PARTICULATE MATTER (PM10) PADA PEDAGANG KAKI LIMA AKIBAT AKTIVITAS TRANSPORTASI (Studi Kasus : Jalan Kaligawe Kota Semarang) - Astri Wulandari; Yusniar Hanani Darundiati; Mursid Raharjo (Jurnal Kesehatan Masyarakat (Undip), 2016)
Kaligawe Street has the highest traffic density according to traffic survey on 2014 which is 6.819,35 passenger car unit/hour. This leading to the amount of emission particularly particulate matter. PM10 is a hazardous particulate which can cause various health problems to death. The estimates concentration of PM10 in 2014 has exceeded the threshold. Thus, it can leading to risk of health problems. The aim of this research is to ascertain the risk of health problems to cadger in Kaligawe Street due to PM10 exposure. This research is an analytical observational research with cross sectional plan and using the method of Environmental Health Risk Assessment. Population on this research are women cadger working in Kaligawe street totaling 53 person. Result obtained, the minimum concentration of PM10 is 41,97µg/Nm3, maximum 104.05 µg/Nm3, and the average 72,42 µg/Nm3. The result of univariate analysis showed 67,9% respondent have time exposure>8 hours/day, 94,3% have frequency exposure 350 days/year, and 73,6% have duration of time≥10 years. The calculation of RQ indicate the average of RQ in minimum concentration is 0,294, maximum concentration 0,728, and average concentration is 0,507. This value is less than 1 (RQ<1), thus, level of risk for women cadger is still safe. The value of RQ > 1 found in maximum concentration are 20,7% of respondent and 9,4% in average concentration. Estimates level of risk in average concentration is no longer safe in the following 15 years, and for maximum concentration is no longer safe in the following 5 years.